Government Regulation Substituting the Law on Job Creation in the Perspective of Constitutional Law - Sulistyowati Sulistyowati; Agus Salim; Puspa Eriyani; Siti Mastoah (Unissula, 2023)
The debate over the Government Regulation in Lieu of Law on Job Creation has not ceased even though it has become an official law. Pros and cons persist due to its perceived deviation from Constitutional Court Decision Number 91/PUU-XVIII/2020, issued on November 25, 2021. This research aims to describe that regulations should not contradict one another, especially when there is already a Constitutional Court decision. Regulations should be made through a legitimate process without resorting to legal shortcuts. The research method used is a normative legal research with a qualitative approach. There is ample time available to follow the proper legislative process, yet shortcuts are taken by issuing Government Regulations in Lieu of Law, which are later ratified as laws. The research implies that despite the enactment of these regulations, there is significant resistance due to their divergence from the judicial review results at the Constitutional Court. As a result, this research suggests the necessity of revising relevant laws to include sanctions for failing to comply with Constitutional Court decision.